Purification and Properties of Prothrombin Modified by Asbestos Filtration of Human Plasma - Izuchi, Y; Boffa, M C; Soulier, J P (Thrombosis and Haemostasis, 1978)
Filtration through asbestos filter (Seitz) of human plasma modified the prothrombin molecule as previously shown. Factor II could no longer be activated by physiological activators (Ca++ + phospholipid + V and Xa) but reacted readily with staphylocoagulase. The separation and purification of the modified prothrombin allowed the preparation of two fractions:A small slightly modified accessory fraction, “prothrombin-asbestos- 1”, lost its ability to be activated by physiological activators, and its ability to be adsorbed by barium citrate, but retained the immunological reactivity of fragment 1, as well as the mobility and molecular weight of unmodified prothrombin.A main fraction, “prothrombin-asbestos-2” appeared to be a modified prothrombin which has lost its N-terminal extremity. It was not adsorbed by barium citrate and could not be activated by physiological activators. It possessed a reduced electrophoretic mobility, as well as a reduced molecular weight (39,000), which are properties similar to those of thrombin. Both fractions 1 and 2 were devoid of thrombin activity.Asbestos was thus able to break the prothrombin molecule non enzymatically, the amputation of the N terminal extremity being responsible for the new functional and physicochemical properties of the molecule.Staphylocoagulase appeared not to need the N terminal extremity of the molecule of prothrombin to form the active thrombin-coagulase complex.